Acaricidal activity of Eruca sativa seed oil and its methanolic extract on Tetranychus urticae (Red form)(Acari:Tetranichidae) - S. Moharramipour; M. Masoumi; Mehdi Ayyari (نامه انجمن حشره‌شناسی ایران, 2019)
In this study, contact toxicity of Eruca sativa (Miller) (Brassicaceae) oil and its methanolic extract were examined on the adult female of Tetranychus urticae (Red form)) (Tetranychidae) at five concentrations and three replications set at 25 ± 1°C, 65 ± 5% RH and 16: 8 h (light: dark). The mortality was evaluated 24 h after treatment. The LC50s of E. sativa oil and the methanol extract were 3062 and 5674 mg L-1, respectively. Measurement of erucin as the main isothiocyanate compound in the oil and methanolic seed extract using high performance liquid chromatography (HPLC) showed that the amount of erucin in the oil was higher than methanol extract. Also, analysis of fatty acids in the oil using gas chromatography (GC) showed that there were 12 types of fatty acids in oil, high level of arachidonic, oleic and Ƴ-linolenic acids. Due to the biological activity and phytochemical analysis, it can be concluded that the higher amount of erucin and fatty acids in the oil, caused the higher acaricidal activity of E. sativa oil compared to methanolic extract. Therefore, our findings showed that the presence of main active phytochemicals in the E. sativa oil plays a decisive role in its efficacy.